Bubbling solutions for the gravitational Maxwell gauged O(3) model in R2. (May 2021) - Choi, Nari; Han, Jongmin
Abstract: In this paper, we construct type II nontopological bubbling solutions of the self-dual equation for the Maxwell gauged O ( 3 ) sigma model coupled with gravity in R 2 . Our solutions blow up at some of the string points or the anti-string points as the coupling parameter tends to zero and they are asymptotically radial near each blow-up point.